2017
DOI: 10.1177/1179554917721710
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Profile and FLT3 Gene Mutations of Childhood Acute Lymphoblastic Leukemia

Abstract: Background:Childhood acute lymphoblastic leukemia (ALL) is characterized by recurrent genetic aberrations. The identification of those abnormalities is clinically important because they are considered significant risk-stratifying markers.Aims:There are insufficient data of cytogenetic profiles in Saudi Arabian patients with childhood ALL leukemia. We have examined a cohort of 110 cases of ALL to determine the cytogenetic profiles and prevalence of FLT3 mutations and analysis of the more frequently observed abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…FLT3 mutations are relatively rare in patients with ALL, with an incidence of 1-7% [19,[27][28][29][30]; they are more common in patients with high diploidy and KMT2A rearrangements [31][32][33]. Univariate analysis in our study revealed that the FLT3 mutation was associated with worse OS, which is consistent with the findings of previous studies that had small samples [19,34,35], However, these studies and ours are limited by the sample size, the short follow-up period, and the different composition of FLT3 mutation types. The effect of the FLT3 mutation on the prognosis of patients with ALL still needs to be confirmed in large-sample clinical studies.…”
Section: Analysis Of the Prognostic Factors Of Patients With B-allsupporting
confidence: 91%
“…FLT3 mutations are relatively rare in patients with ALL, with an incidence of 1-7% [19,[27][28][29][30]; they are more common in patients with high diploidy and KMT2A rearrangements [31][32][33]. Univariate analysis in our study revealed that the FLT3 mutation was associated with worse OS, which is consistent with the findings of previous studies that had small samples [19,34,35], However, these studies and ours are limited by the sample size, the short follow-up period, and the different composition of FLT3 mutation types. The effect of the FLT3 mutation on the prognosis of patients with ALL still needs to be confirmed in large-sample clinical studies.…”
Section: Analysis Of the Prognostic Factors Of Patients With B-allsupporting
confidence: 91%
“…For instance, Zheng et al reported that FLT3 and TP53 mutations are common in Chinese ALL patients ( 31 ), and Zhang et al reported high rates of FLT3 mutations in B-ALL ( 32 ). In contrast, a lower rate of FLT3 mutations (4–5%) has been reported in international studies ( 33 , 34 ). In our study, all TP53 mutant chromosomes had a normal karyotype, although previous studies have shown that TP53 mutations usually occurred in hypodiploidy.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, it was 99.7% in the study by Dastugue et al [85]. It is believed that this is related to the potentially greater sensitivity of hyperdiploid lymphocytes to the cytotoxic effects of methotrexate, which is a component of many currently used therapies [28,75,86,87].…”
Section: High Hyperdiploidymentioning
confidence: 83%